Halalpreneurs among immigrants and their business prospects in Malaysia - Abdullah, Moha Asri (2018)
Immigrant entrepreneurial involvements in economic activities have been well noted. Scholars tend to agree that the presence, and contribution of immigrant entrepreneurs to business and growth of new businesses lead to economic prosperity, job creation, multiple monetary benefits and overall economic well-being. The immigrant-entrepreneurial activities are found in many countries, developing and developed alike. However, immigrant who involve in halal entrepreneurship or halalpreneurs is less known. Immigrant Halalpreneurs, their business success and business prospects are not found, discussed and researched. In constrast, immigrant entrepreneurial activities and halal industry are both growing tremendously over decades, globally and domestically. This study aims to identify issues and challenges of immigrant halalpreneurs, and their business success and prospects in small retailing businesses. Based on 274 immigrant halalpreneurs surveyed at Klang Valley, Malaysia, it was found that the majority of immigrant halalpreneurs come from Bangladesh, Pakistan, and Indonesia. Immigrant halalpreneurs are found to be relatively well prepared for business and obtained experience before initiating a business. They are positive about their business issues as well as business success and prospects, with the highly significant relationship between those variables. The research concludes that immigrant halalpreneurs and their business activities can be a source of entrepreneurial development, employment generation and future impetus for economic growth and development.